2005
DOI: 10.1073/pnas.0505945102
|View full text |Cite
|
Sign up to set email alerts
|

Measles virus replication in lymphatic cells and organs of CD150 (SLAM) transgenic mice

Abstract: A transgenic mouse containing the complete human SLAM (hSLAM͞CD150) gene, including its endogenous promoter for transcription, was generated by using human genomic DNA cloned into a bacterial artificial chromosome. hSLAM, the primary receptor for measles viruses (MV), was expressed on activated B, T, and dendritic cells with an expression profile equivalent to that of humans. We demonstrated that hSLAM ؉ cells obtained from the transgenic mouse, including activated B, T, and dendritic cells, were susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…Bone marrow-derived DCs (BMDCs) were used to study MV permissiveness of DCs, initially in CD150Tg mice (Ohno et al, 2007, Shingai et al, 2005, Welstead et al, 2005. Studies using BMDCs from CD150Tg mice in combination with Mavs -/-, Irf3 -/-/Irf7 -/-, Ticam1 -/-and Myd88 -/-mice showed that type I IFN expression in BMDCs completely relied on MAVS but not TICAM-1 and MyD88 (Takaki et al, 2014).…”
Section: Studies In Mice With Targeted Gene Deletions Provide Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow-derived DCs (BMDCs) were used to study MV permissiveness of DCs, initially in CD150Tg mice (Ohno et al, 2007, Shingai et al, 2005, Welstead et al, 2005. Studies using BMDCs from CD150Tg mice in combination with Mavs -/-, Irf3 -/-/Irf7 -/-, Ticam1 -/-and Myd88 -/-mice showed that type I IFN expression in BMDCs completely relied on MAVS but not TICAM-1 and MyD88 (Takaki et al, 2014).…”
Section: Studies In Mice With Targeted Gene Deletions Provide Insightmentioning
confidence: 99%
“…Both attachment and infection of immature DCs with MV are blocked by DC-SIGN inhibitors, suggesting that DC-SIGN is critical for enhancement of CD46/CD150-mediated infection of DCs (de Witte et al, 2006). Human CD150 transgenic (Tg) and CD150 knock-in mice were generated as MV infection models to study receptor tropism and the immune dynamics of MV (Hahm et al, 2003, Hahm et al, 2004, Ohno et al, 2007, Sellin et al, 2006, Shingai et al, 2005, Welstead et al, 2005 and these mice were somehow permissive to MV in vivo. Systemic infection by WT strains of MV in vivo was observed in CD150Tg/Ifnar -/-mice, generated by crossing CD150Tg mice with mice having the disrupted IFN receptor 1 (Ifnar) gene; the other is CD150Tg/Stat1 -/-mice, generated by crossing CD150Tg mice with mice knocked out for the signal transduction and activator of transcription 1 (Stat1) gene, which is a major signaling molecule for the IFN receptor (Shingai et al, 2005, Welstead et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that the SeV C protein To what extent its IFN antagonists V, C, and P proteins can interact with their target protein counterparts in mouse cells remain to be defined. Thus, in addition to cellular receptors, the ability to counteract the host IFN response is an important determinant for the host range of MV (15,(18)(19)(20)23). …”
Section: Discussionmentioning
confidence: 99%
“…Several transgenic or knock-in mice expressing human SLAM or CD46 have been generated as small animal models for measles (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). To facilitate MV replication, these mice usually have to be made defective in IFN signaling (16,(18)(19)(20) or used when they are newly born (15,17). Similarly, when human SLAM or CD46 is expressed by transfection, rodent cells become susceptible to MV, but do not allow MV growth as efficiently as primate cells (14,26).…”
mentioning
confidence: 99%
“…BAC DNA inserts, typically 100-300 kb, are more likely to contain the complete set of regulatory elements required for tissue-specific and position-independent transgene expression. Examples of transgenic mice with cell-specific expression from BAC transgenes include mice with expression of human coagulation factor V restricted to platelets and liver (12) and mice that have a human-like tissue expression profile of hSLAM, the primary receptor for measles viruses (13). In the article by Ranatunga et al, the hIL-10BAC was faithfully expressed in myeloid cells, rescuing IL-10-deficient mice from lethal endotoxin shock.…”
Section: Myeloid But Not T Cells Express Hil-10bacmentioning
confidence: 99%